Accessibility and usability analysis of online museum's graphical user interface - Karol Łazaruk; Kacper Majcher; Maria Skublewska-Paszkowska (Journal of Computer Sciences Institute)
The aim of this paper was to analyse the accessibility and usability of the graphical user interface of web services: the proprietary web application implemented with the principles of universal design and the website of the Biłgoraj Land Museum not meeting these principles. The experiment involved 15 participants and consisted of two parts: the eye tracking and the surveys. In the first one, an eye tracker was used to acquire times to the first fixation of the area of interest, fixation count and scan paths. The second one used the LUT and QUIS surveys to examine the usability and respondents’ satisfaction with both systems. It was proven that the time to locate the elements is shorter for a system meeting the principles of universal design. It was found that satisfaction with the interface rises when it is adjusted to the user's main needs.